The Anti-Corruption Mechanisms and Measures - Ochilov Tokhtamishovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The fight against corruption remains one of the most urgent issues of today's world. The fight against this disease covers many countries of the world. Many practical works are being done in the fight against corruption in the countries of the world. Currently, a number of programs have been adopted in different countries as part of the fight against corruption, and extensive work is being carried out on them. The article examines the experience of the countries of the world in fighting corruption.